Comprehensive analysis of semantic structural similarity of idioms in four languages: Russian, English, French, German - Kabalina, Olesya; Baturina, Elvira; Borovkova, Irina (International Journal of Psychosocial Rehabilitation, 2020)
This article is devoted to the study of idiomatic expressions for their semantic-structural similarity in English, German, French and Russian. The purpose of the study is to identify the features of the interaction of languages at the level of indivisible phrases, to establish commonalities and differences in the structures of expressions, to analyze the results and their explanation. Using the main, basic methods of comparative and etymological analysis, language pairs were identified that show tendencies towards the greatest and least similarity at the level of idioms; completely matching phrases were found in four languages, and idioms were revealed that did not coincide in the selected languages at the same time. The study also used the Google Books Ngram Viewer program, which made it possible to find out the dates of the appearance of some idioms in the large body of literature of the corresponding languages (from 1600 to 2012) to explain the results of the revealed equivalence of some expressions. The results obtained also demonstrate that the belonging of languages to the same language group is not a guarantee of the greatest number of coincidences of idioms in these languages in terms of structure and semantics of individual elements.